2019
DOI: 10.5430/jnep.v9n11p85
|View full text |Cite
|
Sign up to set email alerts
|

A novel in-service nursing education optimizing theory of technological competency as caring in nursing

Abstract: Contemporary and future nursing practices are increasingly being designed with nursing theories as to its foundation. The aim of this article is to describe an in-service education program for nursing administrators centered on the theory of Technological Competency as Caring in Nursing (TCCN). This theory is framed chiefly within the concepts of technology, caring, nursing, and technological competency. Influencing the significance of in-service education is theory-based practice with advancing technologies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Table 1 shows the characteristics of the studies included and their classification in the hierarchy of evidence. The literature included was ranked with the fourth ( 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ), fifth ( 2 , 23 ), sixth ( 1 , 6 , 24 25 ) and seventh ( 3 , 4 , 5 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ) hierarchy of evidence levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 shows the characteristics of the studies included and their classification in the hierarchy of evidence. The literature included was ranked with the fourth ( 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ), fifth ( 2 , 23 ), sixth ( 1 , 6 , 24 25 ) and seventh ( 3 , 4 , 5 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ) hierarchy of evidence levels.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the increasing development of technology in our environment, Locsin’s theory could be applied to all areas of nursing. Technology is increasingly present in education, so it is necessary to also educate and develop technological competence in this field ( 4 , 22 , 25 , 26 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that education in TCCN theory improves awareness and understanding of TCCN theory (Nakano et al, 2019(Nakano et al, , 2021. It cannot be denied that the experience of being educated in TCCN theory may affect the results of the survey.…”
Section: Differences Between Perception and Practice Dimensionmentioning
confidence: 97%
“…In addition, his team has developed the Technological Competency as Caring in Nursing Instrument-Revised (TCCNI-R) for use in both the Japanese and English languages. Nakano et al (2019Nakano et al ( , 2021 used the Japanese version of TCCNI-R to investigate the educational effects of TCCN theory on nursing administrators and found that teaching TCCN theory improved nursing administrators' understanding and perception of TCCN theory. Also, Yokotani et al (2021) evaluated the Japanese version of the TCCNI-R by exploratory and confirmatory factor analysis by employing SEM to test for construct validity, and Cronbach's alpha confirmed its reliability.…”
Section: Introductionmentioning
confidence: 99%